Adaptabilitas Hukum Islam Terhadap Perubahan Sosial : Studi Pemikiran Abu Ishaq al-Shatibi - Yoyo Hambali (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2015)
The title of this article is, "Adaptability of Islamic Law and Social Change: Study of Abu Ishaq al-Shatibi Thought!". This paper is a summary and critical analysis on the dissertation work of Muhammad Khalid Mas’ud, entitled "Islamic Legal Philosophy: A Study of Abu Ishaq al-ShatibPs Life and Thought". This dissertation submitted to the Doctor of Philosophy Program Institute ofIslamic Studies at McGill University, Montreal, in March 1973. The conclusion of this article that the concept ofmaslahah and maqasid al-shaii’ah be studied not only in theory but also the level of crmch-is precisely in line with the growing interest academic and practical needs of law that became a phenomenon in almost all Islamic countries. The doctrine maqasid al-shan'ab of al-ShatiU is an attempt to enforce ma?la}fah as an essential source for legal purposes. According to al-Shatibi, the main purpose ofIslamic law is a human tnaflabah. Obligations under the sharia are noticed maqasid ai-shan'ah in which he changed in order to protect human benefit.